(untitled) (Research, Society and Development, 2022)
The objective of this work is to evaluate the production of self-adensible cementitious composite with the residues of ground glass, in the proportions of 5%, 10%, 15%, 20% and 30% in place of the kid aggregate and investigate its physical and mechanical properties. Concrete is one of the most used materials in civil construction and many types of waste can be used in its composition to reduce the extraction of natural raw materials, such as glass which is a 100% recyclable material and can be used as aggregate in cementitious composite or glass powder in cement making cement. For this, the tests of granulometry, specific mass, unit mass, mass will be used for the characterization of glass residue. In the fresh state, the "Mini-Cone Slump Flow" and "mini v-funnel test" methods were performed to obtain viscosity and spreading diameter index and in the hardened state were performed mechanical strength tests to axial and diametric compression, specific mass and void stake. The results obtained indicate that the compressive strength decreased with the increase of compressive strength at 28 days.